DETECTION OF CHRONIC TYPHOID CARRIERS AMONG FOOD HANDLERS IN WAD MEDANI , GEZIRA STATE , SUDAN - B. M. Osman, Mohammed; Edriss, Ali A.; El-mahdy, Ebrahim E.; M. Mekki, Abdelwhab (مجلة الجزيرة للعلوم الصحية; مجلد 7 عدد 1 (2011), 2011)
Typhoid fever remains a disease of major public health importance in the tropics. This cross sectional prospective descriptive study was carried out between July 2005 to July 2008 in Wad Medani Town. The objective of the study was to identify chronic typhoid carriers among food handlers in Wad Medani. To achieve this objective, Vi agglutination test was used to determine suggested typhoid carriers among food handlers then stool culture was performed on those with a positive Vi agglutination test. A questionnaire was designed to collect data from suggested typhoid carriers about hygienic practices during food handling and processing .  The collected data were reviewed and coded. Data were analyzed using SPSS versions 10.0 software for tabulation and statistical analysis. The results showed that, ten percent of the examined food handlers were found positive typhoid carriers by Vi agglutination test, 48.5% of the suspected of typhoid carriers were found positive by stool culture, street vendors were more common among suspected typhoid carriers, all of whom had not received any health education about typhoid disease. The study suggested the following recommendations: Regular health authority inspection visitor food handling personnel specially street vendors to exclude typhoid carriers among them, education and training course in good hygienic practices should be provided to all food handlers specially typhoid carriers by Food Control Department, Ministry of Health, Gezira State.